2010
DOI: 10.1007/s10803-010-0975-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Problems, Psychiatric Symptoms, and Quality of Life for Older Adults With Intellectual Disability With and Without Autism

Abstract: The evidence base on outcomes associated with autism in older adulthood is limited. The expected increase in the prevalence of older adults with autism highlights the need to describe their profiles and service needs. Adults 50 years or older with an intellectual disability (ID) and the triad of impairments characteristic of autism spectrum disorders (ASD) were compared to peers with ID only, and younger adults with ASD and ID. After accounting for ability differences, older adults with ASD did not differ from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 48 publications
(57 reference statements)
3
84
1
2
Order By: Relevance
“…These results are in line with findings in the international literature (Izard et al, 2006;Mayer, Roberts, Barsade, 2008;Sappok et al, 2014;Matson 2009a,b;Totsika 2010). Divergent from the design in which we used the setting of a team, the intra-and inter-raterreliability was based on scores given by single team members.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in line with findings in the international literature (Izard et al, 2006;Mayer, Roberts, Barsade, 2008;Sappok et al, 2014;Matson 2009a,b;Totsika 2010). Divergent from the design in which we used the setting of a team, the intra-and inter-raterreliability was based on scores given by single team members.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, an integrative approach, combining pedagogical, psychological, pharmaceutical, and social treatment and support methods is warranted (Dosen, 2007). From this point of view, it might be relevant in terms of an efficient therapeutic process to evaluate the level of development in different dimensions, including cognitive functions, social-adaptive behaviour, and emotional abilities (La Malfa, 2009;Matson, 2009a,b;Totsika, 2010;Sappok, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This higher rate of acceptance can lead to more opportunities such as employment, personal relationships, and other forms of community inclusion [3]. This integrative mindset can help individuals feel as though they are a part of the community in which they live, which can lead to higher rates of self-esteem and mitigate depression [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors have also been suggested to be related to outcome, including symptom severity, repetitive/stereotyped behaviors in childhood, adaptive behavior, education, gender, the presence of a diagnosed medical disorder, onset of epilepsy before age 5 years, and joint attention skills (Billstedt et al 2007;De Meyer et al 1973;Farley et al 2009;Gillespie-Lynch et al 2012;Howlin and Goode 1998;Totsika et al 2010;Venter et al 1992). For instance, Farley et al (2009) reported that adaptive behavior measures (in particular the Daily Living Skills domain) evaluated at follow-up were most closely correlated to better outcomes.…”
Section: Predictors Of Adult Independencementioning
confidence: 99%
“…Totsika et al (2010) found that an older (50 years or older) group of adults with ASD and ID presented with fewer behavioral problems than the younger (<50 years) group, which is consistent with reports of decreases in behavior problems in the general adult intellectual disability population (Holden and Gitlesen 2006). Billstedt et al (2007) found that social interaction problems were still present in the vast majority of adults with ASD, but the occurrence of behavioral impairments (maladaptive and stereotyped behaviors) was much more variable with only a few symptoms in each category affecting half or more of the study sample.…”
Section: Diagnostic Stability and Symptom Severitymentioning
confidence: 99%